Overexpression, purification, crystallization and crystallographic analysis of CopK of Cupriavidus metallidurans - Tricot, Catherine (International Union of Crystallography, 2005)

(untitled)
CopK of Cupriavidus metallidurans is a 93-amino-acid protein whose mature form (73 amino acids) has been purified and crystallized by the hanging-drop vapour-diffusion method in 100 mM citrate pH 3.5, 200 mM Li(2)SO(4), 20%(w/v) glycerol, 13%(w/v) PEG 8000. Crystals display orthorhombic symmetry, with unit-cell parameters a = 57.53, b = 128.65, c = 49.77 Å, and diffract to 2.2 Å resolution using synchrotron radiation.